Evaluation of Cash and Credit Sales Accounting Systems at Motorcycle Dealers: Evaluasi Sistem Akuntansi Penjualan Tunai dan Kredit di Dealer Sepeda Motor - Fitriana Yogi Novianti; Aisha Hanif (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Accounting information systems play a crucial role in supporting operational control and financial decision-making in trading companies. Specific Background Many small-scale motorcycle dealers still rely on manual systems for cash and credit sales, which may increase operational risk and weaken internal control. Knowledge Gap Limited empirical evaluations address how manual accounting systems affect sales procedures and profitability in used motorcycle dealerships. Aims This study aims to evaluate the accounting information system for cash and credit sales at UD Be’y Motor Tanggulangin Sidoarjo. Results The findings indicate that the existing manual system creates operational inefficiencies, increases credit risk, and limits internal financial control, particularly due to dependence on external leasing for receivable management. Novelty This study provides a detailed evaluation of cash and credit sales accounting practices in a used motorcycle dealer context while linking system limitations to operational and profitability risks. Implications The study recommends adopting simple accounting software and improving system integration to strengthen internal control, reduce risk, and support sustainable business operations. Keywords: Accounting Information System, Cash Sales, Credit Sales, Internal Control, Motorcycle Dealer Key Findings Highlights: Manual recording practices limit financial control and data reliability Credit sales procedures rely heavily on external leasing management System improvements are required to reduce operational and credit risks